Glial and light-dependent glutamate metabolism in the suprachiasmatic nuclei - Leone, Maria Juliana (2015)
The suprachiasmatic nuclei, the main circadian clock in mammals, are entrained by light through glutamate released from retinal cells. Astrocytes are key players in glutamate metabolism but their role in the entrainment process is unknown. We studied the time dependence of glutamate uptake and glutamine synthetase (GS) activity finding diurnal oscillations in glutamate uptake (high levels during the light phase) and daily and circadian fluctuations in GS activity (higher during the light phase and the subjective day). These results show that glutamate-related astroglial processes exhibit diurnal and circadian variations, which could affect photic entrainment of the circadian system.